FUNDAMENTALS OF THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF STUDENTS OF LAW PEDAGOGICS - Khamrakulov Zafarjon Yigitalievich (Journals Park Publishing, 2022)
The article analyzes the foundations of the formation of professional competence of students of legal educators. The problems and shortcomings in the development of professional competence of students and ways to overcome them are studied. At the end of the article, conclusions are given about the foundations for the formation of professional competence of students of legal educators.
Keywords: professional competence, teacher, specialist, jurisprudence, higher education, student, offense, pedagogical education, theoretical knowledge.